12-(3x-6)-5(7-x)=

Simple and best practice solution for 12-(3x-6)-5(7-x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-(3x-6)-5(7-x)= equation:


Simplifying
12 + -1(3x + -6) + -5(7 + -1x) = 0

Reorder the terms:
12 + -1(-6 + 3x) + -5(7 + -1x) = 0
12 + (-6 * -1 + 3x * -1) + -5(7 + -1x) = 0
12 + (6 + -3x) + -5(7 + -1x) = 0
12 + 6 + -3x + (7 * -5 + -1x * -5) = 0
12 + 6 + -3x + (-35 + 5x) = 0

Reorder the terms:
12 + 6 + -35 + -3x + 5x = 0

Combine like terms: 12 + 6 = 18
18 + -35 + -3x + 5x = 0

Combine like terms: 18 + -35 = -17
-17 + -3x + 5x = 0

Combine like terms: -3x + 5x = 2x
-17 + 2x = 0

Solving
-17 + 2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '17' to each side of the equation.
-17 + 17 + 2x = 0 + 17

Combine like terms: -17 + 17 = 0
0 + 2x = 0 + 17
2x = 0 + 17

Combine like terms: 0 + 17 = 17
2x = 17

Divide each side by '2'.
x = 8.5

Simplifying
x = 8.5

See similar equations:

| 39-w=2 | | y-65=9 | | (4t+9)-(-2+7)=0 | | A=p+pnr | | p-10=25 | | 8=n-65 | | 52q=32 | | b^4-ab^3+b^2c=0 | | 7*cos^2*x-cos*x-8=0 | | 71=-9n+8 | | 3*cos*2*x-5*cos*x-1=0 | | -3(y-2)=-5y+18 | | 7w-9=5(w+1) | | 7(y+6)-2y=2 | | 22-2x=14 | | .5x-2.4=.6 | | -4v+8(v-2)=-4 | | -3(4t-3)+5t=6t-5 | | 48+x(9+3)=288 | | 7u+5=5 | | -4v+8(v+2)=-4 | | 8g-7=-39 | | 3y+2f-f+1-3y+7=32 | | 2k+5=3 | | -5n+3=-4n-4 | | -6=-6w+4(w+3) | | 4b^2-169y^2= | | 9x+3x=10101010101001101 | | c+bc-11c-4=13c+4-2 | | 2k+10=k+15 | | (8/t-7)-3/t | | 15=2a-2 |

Equations solver categories